2020
DOI: 10.1002/essoar.10505558.1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impoundment-associated Hydro-mechanical Changes and Regional Seismicity near the Xiluodu Reservoir, Southwestern China

Abstract: This page was generated automatically upon download from the ETH Zurich Research Collection. For more information please consult the Terms of use. ETH LibraryFour major hydropower stations (Wudongde, Baihetan, Xiluodu, and Xiangjiaba) have recently been built along the Jinsha River, Southwestern China (Figure 1). They all rank among the top five largest hydropower stations in China, with a total installed capacity of ∼43 GigaWatt.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 79 publications
0
2
0
Order By: Relevance
“…On the basis of geophysical logs and field testing in the West Shale Basin in Canada, they developed a quantitative 3D stress distribution model for determining the maximum and minimum horizontal stress, vertical stress, stress orientation, as well as ambient pore pressure. These variables are then used to evaluate the mechanical stability of the faults in the area of interest (Snee & Zoback, 2018; Zhang et al., 2021). Seismic hazard forecasts rely on the assessment of historical natural earthquakes and probabilities of earthquake magnitudes, frequency, location, as well as ground mechanical properties (Cornell, 1968).…”
Section: Future Research Opportunitiesmentioning
confidence: 99%
“…On the basis of geophysical logs and field testing in the West Shale Basin in Canada, they developed a quantitative 3D stress distribution model for determining the maximum and minimum horizontal stress, vertical stress, stress orientation, as well as ambient pore pressure. These variables are then used to evaluate the mechanical stability of the faults in the area of interest (Snee & Zoback, 2018; Zhang et al., 2021). Seismic hazard forecasts rely on the assessment of historical natural earthquakes and probabilities of earthquake magnitudes, frequency, location, as well as ground mechanical properties (Cornell, 1968).…”
Section: Future Research Opportunitiesmentioning
confidence: 99%
“…We note that our seasonal results show increased Coulomb stress changes than the two previously mentioned studies due to the much larger and more condensed volume of water as well as the fact that our model derives stress on idealized fault planes (as opposed to actual fault geometries that are likely not oriented in such an idealized manner). Further, recent work by Zhang et al (2020) where they modeled Coulomb stress changes from reservoir loading and unloading in China has shown that stress changes on the order of 1-100 kPa were found ranging from the surface down to depths of 15 km. These stresses were modeled according to the typical fault geometries in the region and are more aligned with the results from within this research.…”
Section: Seasonal Operationsmentioning
confidence: 99%